PLEISTOCENE BIOGEOCHEMICAL RECORD IN THE SW PACIFIC OCEAN (IMAGES SITE MD97 - 2114, CHATHAM RISE) - Cobianchi M.; Lupi C.; Mancin N.; F. Lirer; Pelosi N.; Trattenero I.; Bordiga M.; Hall I. R.; Sprovieri M.; LUCIANI, Valeria (Journal of Quaternary Science, 2012)
Through a multidisciplinary approach based on micropaleontological and geochemical analyses, the main paleoceanographic and paleoclimate changes that have influenced the surface- and deep-water circulation in the South West Pacific Ocean (Chatham Rise, eastern New Zealand) during the last 1Ma are here reconstructed. This region represents a key area for investigating the climate evolution during the Pleistocene because here the largely wind-driven Antarctic Circumpolar Current (ACC) interacts with the west Pacific Ocean circulation via Deep Western Boundary Current (DWBC), the major source of deep water for the whole Pacific Ocean. In order to understand coupling or decoupling events between sea surface and bottom waters a continuous marine sedimentary succession of the last 1.1 Ma, recovered by the IMAGES (International Marine Past Global Change Study) cruise in the Southwest Pacific Ocean (Core MD 97-2114), has been investigated in its calcareous planktic and benthic microfossil content and C and O isotope record performed both on planktic and benthic foraminiferal tests. Results show the occurrence of long- and short-term patterns of climate and ocean circulation in the last one million years as the result of the interplay of ice-sheet dynamics, surface tropical versus polar water inflow and trophic status of the surface water.